2020
DOI: 10.1007/s12016-020-08810-9
|View full text |Cite
|
Sign up to set email alerts
|

Are Physicochemical Properties Shaping the Allergenic Potency of Plant Allergens?

Abstract: This review searched for published evidence that could explain how different physicochemical properties impact on the allergenicity of food proteins and if their effects would follow specific patterns among distinct protein families. Owing to the amount and complexity of the collected information, this literature overview was divided in two articles, the current one dedicated to protein families of plant allergens and a second one focused on animal allergens. Our extensive analysis of the available literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 222 publications
(359 reference statements)
2
124
0
Order By: Relevance
“…All of this leads to an impaired digestion, intestinal uptake of food proteins, and increase of their ability to cause allergic reactions. Recent studies showed that lipid ligands could also affect physicochemical and immunogenic features of proteins [ 4 ]. In our study, we showed that the lentil Len c 3 food allergen was sensitive to heating and digestion, but the presence of its possible endo- and exogenic lipid ligand might increase the protein thermostability during food cooking, decrease the rate of its gastroduodenal degradation, and, as a result, retain its IgE-binding capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of this leads to an impaired digestion, intestinal uptake of food proteins, and increase of their ability to cause allergic reactions. Recent studies showed that lipid ligands could also affect physicochemical and immunogenic features of proteins [ 4 ]. In our study, we showed that the lentil Len c 3 food allergen was sensitive to heating and digestion, but the presence of its possible endo- and exogenic lipid ligand might increase the protein thermostability during food cooking, decrease the rate of its gastroduodenal degradation, and, as a result, retain its IgE-binding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that interaction of food allergens with their ligands leads to structural changes that affect their stability and allergenic properties. Lipid ligands change the process of degradation of lipid-binding food allergens in the human gastrointestinal tract, affect their passage through epithelial barriers, and reduce or increase the efficiency of their interaction with IgE [ 3 , 4 ]. The formation of lipid–protein complex may occur in a natural source of allergen, during cooking or in a human gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Food processing can induce several chemical and structural modifications in lupine proteins, affecting their allergenicity by the alteration of some epitopes or the exposure of new ones (Figure 1) (Loza & Lampart-Szczapa, 2008). Similarly, the occurrence of chemical reactions among proteins, fat, and sugars, in the food matrix, can restrict the protein availability to interact with the immune system, reducing their allergenicity, but it can also decrease protein digestibility (preserving the existing epitopes), potentially increasing protein allergenicity (Costa et al, 2020;. Although there are some studies reporting the influence of food processing, food matrix, and digestibility on the allergenicity of lupine proteins (summarized in Table 3), the existing information is still insufficient.…”
Section: Effect Of Processing Food Matrix and Digestibility On Lupimentioning
confidence: 99%
“…Indirect analysis (immunoblotting, inhibition ELISA, among others) is based on the use of patients' sera, meaning that this assessment is more prone to bias because a patient positive to specific IgE does not necessary lead to clinical allergic symptoms. Patients' sera are affected by several intrinsic (age, sex, presence of concomitant diseases, genetic heritage, among others) and environmental (such as geographical origin) factors, which cannot be ruled out when evaluating the allergenic potential of different proteins (Costa et al, 2020). Regarding lupine allergens, it became clear that some molecules are more prone to lose their allergenicity upon processing and/or digestion (such as α-conglutin and β-conglutin), whereas others may preserve their clinical reactivity (such as γconglutin).…”
Section: Effect Of Processing Food Matrix and Digestibility On Lupimentioning
confidence: 99%
“…Food allergies have become a concrete and widespread public health problem, reaching “near-epidemic proportions” in some regions of the world [ 1 ]. Cow milk allergy is among the most common food allergies, affecting between 0.6% to 3% of children below the age of 6 years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%